Talk to strangers how everyday, random encounters can expand your business, career, income, and life - Topus, David, 1956- (Tantor Media, 2020)
By bringing in hundreds of thousands--maybe millions--of dollars of sales, speaking engagements and other opportunities through meetings with remarkable influential men and women author David Tupos has learned firsthand how every day, random encounters really do change lives; that is, if you know how to make them happen the right way and monetize the connection at the other end. From the moment you walk out your door in the morning, there is a world of opportunity waiting for you if you know how to access it. As readers will learn in order to stand out and maximize the potential of others within and even outside traditional sphere of influence, you must take notice of who is standing alongside you on the bank line, the latte pickup point, or the dryer at the Laundromat. David Topus' life-changing message is that we must "always connect," and that means breaking out of the Matrix-like web of virtual, yet often impersonal, reality to real life encounters with the outside world in meaningful exchanges that have unlimited potential to supercharge income, accelerate careers and enrich readers' livesforever. Readers will learn Why there is opportunity for you wherever you go New places to connect and build your pipeline The four beliefs of successful random connectors Opening statements that lead to productive conversations Techniques for creating comfort and trust quickly Ways to create high perceived value for yourself and what you offer How to optimize and monetize your newly-established contacts.